The objectives of sharīʿah in nomination for the payment of family takaful benefits - Salleh, Safinar; Halim, Akmal Hidayah; Ibrahim, Uzaimah; Abdullah, Mohamad Asmadi (Emerald Publishing Limited, 2019)
A family takaful certificate is subscribed by a takaful participant for the purpose of preparing financial support for his dependants after his death. The takaful benefits could then be made payable to a nominee named as the beneficiary under conditional hibah (gift). In this respect, the participant is free to decide to whom the benefits are to be given since the law is silent as to the criteria of the beneficiary. This situation gives rise to the issue on whether such a practice fulfils the objectives of Sharīʿah, especially when the nominated beneficiary is not the sole dependant of the deceased participant. Therefore, this research aims to evaluate the status of family takaful benefits, analyse the rules of conditional hibah from the Sharīʿah perspective and propose solutions whenever necessary. The research adopts doctrinal analysis by examining existing primary and secondary materials including statutory provisions and other legal and non-legal literatures. The study predicates that the application of conditional hibah to the whole benefits does not reflect the objectives of Sharīʿah if determination on the status of the benefits is solely based on the nomination made by the participant. It is observed that takaful benefits payable from the Participant’s Account should be considered as the deceased’s estate and must be distributed according to fara’id or Islamic law of inheritance. Conversely, the sum covered payable from the Participant’s Special Account may be paid to the deceased’s dependents whose criteria are determined by the Sharīʿah Advisory Council as the highest authority in Islamic financial matters.